1994
DOI: 10.1128/mcb.14.9.6244
|View full text |Cite
|
Sign up to set email alerts
|

Simian virus 40 small t antigen cooperates with mitogen-activated kinases to stimulate AP-1 activity.

Abstract: The simian virus 40 small tumor antigen (small t) specifically interacts with protein phosphatase type 2A (PP2A) in vivo and alters its catalytic activity in vitro. Among the substrates for PP2A in vitro are the activated forms of MEK and ERK kinases. Dephosphorylation of the activating phosphorylation sites on MEK and ERKs by PP2A in vitro results in a decrease in their respective kinase activities. Recently, it has been shown that overexpression of small t in CV-1 cells results in an inhibition of PP2A activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 57 publications
6
55
0
Order By: Relevance
“…Various constitutively active components of the Ras/Raf/MEK pathway were used to activate Elk-1 transactivation. They included H-Ras-V12, Raf-1(BXB), which only contains the Raf-1 kinase domain (26), Raf-1(CAAX), which is constitutively targeted to plasma membrane by fusing Raf-1 with the C terminus of H-Ras (27), and MEK1(DD) (28). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Various constitutively active components of the Ras/Raf/MEK pathway were used to activate Elk-1 transactivation. They included H-Ras-V12, Raf-1(BXB), which only contains the Raf-1 kinase domain (26), Raf-1(CAAX), which is constitutively targeted to plasma membrane by fusing Raf-1 with the C terminus of H-Ras (27), and MEK1(DD) (28). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Small t shares 82 aminoacids at its aminoterminus with Tag; the remaining 92 amino acids are unique. Small t enhances the transforming capacity of SV40 by increasing the production of Tag (Bikel et al, 1987); by contributing to the complete inactivation of cellular p53 (Tieman et al, 1995); and by stimulating mitosis in quiescent cells (Cicala et al, 1994), an e ect that may be mediated by the ability of small t to induce AP-1 (Frost et al 1994). In 1979, Lewis and Martin demonstrated that small t mutants injected subcutaneously (sc) into hamsters induced sarcomas with a prolonged latency compared to wild-type (wt) SV40 (Lewis and Martin, 1979).…”
Section: Sv40 and Mesotheliomamentioning
confidence: 99%
“…The phosphotyrosines act as docking sites for SH2 and PTB domain-binding cellular proteins like the lipid kinase phosphatidylinositol 3-kinase (PI 3-kinase) (Whitman et al, 1985), the adaptor protein SHC Campbell et al, 1994) and phospholipase C-g1 (PLC-g1) (Su et al, 1995). In addition, the serine/threonine speci®c phosphatase 2A (PP2A) (Walter et al, 1990;Pallas et al, 1990) and a member of the 14-3-3 family of proteins have been found to associate with middle-T. PP2A, a ubiquitously expressed cellular phosphatase, is also known to bind to SV40 or polyoma small-T and has been shown to interfere with downregulation of ERK1 and ERK2 (Sontag et al, 1993;Frost et al, 1994). C-Src as well as 14-3-3 have been implicated in the activation of Raf (Marais et al, 1995;Freed et al, 1994;Irie et al, 1994;Fu et al, 1994;Li et al, 1995).…”
Section: Introductionmentioning
confidence: 99%